Hubungan Antara Status Gizi Balita Dengan Kejadian Ispa (Infeksi Saluran Pernapasan Akut) Pada Balita Di Puskesmas Karanglewas - Misrina Retnowati (Viva Medika, 2019)
Abstract Age toddlers are the most vulnerable groups with respiratory infection. Mortality survey conducted by the Subdit Tract Infection Acute Respiratory put Tract Infection Acute Respiratory /Pneumonia as a cause of infant mortality in the spread Indonesia with a percentage of 22.30% of all under-five deaths. This disease is influenced by several factors such as nutritional status. Status Nutrition is one of the indicators that describe the level of welfare of the community. The purpose of this research was to determine the Relationship Between Nutritional Status Of Toddlers With The Incidence Of Tract Infection Acute Respiratory On Toddlers In Puskesmas Karanglewas. This research uses a survey analytic methods with retrospectivecase control design approach. This research is done at the Puskesmas Karanglewas. The population is all children aged 1-5 years who suffer Tract Infection Acute Respiratory is 1501 cases and 232 do not suffer from Tract Infection Acute Respiratory as controls. The sample is comparable to the 94 for cases and 94 for control. The technique of sample collection is by using purposive sampling and simple random sampling technique. The data analysis with chi-square test. The analysis result is the majority of children under five suffering from malnutrition Tract Infection Acute Respiratory A total of 40 infants (42.6%). Statistical calculation results show value p-value = 0.000 while the value of α= 0.05 so that the p-value < 0.05 which means that there is a relationship between the nutritional status of toddlers with the incidence of Tract Infection Acute Respiratory on toddelrs. Conclusion there are a relationship between the nutritional status of toddlers with the incidence of Tract Infection Acute Respiratory on toddlers in Puskesmas Karanglewas Keywords: nutritional status toddler, Tract Infection Acute Respiratory